ANALISIS VICTIMS PRECIPITATION THEORY TERHADAP ANAK KORBAN PROSTITUSI ONLINE (MICHAT) DI KOTA PONTIANAK - NIM. A1012191048, MARISA KURNIATY (Jurnal Fatwa Hukum, 2024)
Abstrac  Technological advances provide various benefits for human life. One of the benefits obtained through technological progress and development is the breadth of access to event information, learning information and even information on trade in goods and services through just one or several applications. However, this breadth of access also has a negative impact on social life, where this freedom makes it easier for everyone to carry out prostitution transactions online. This has a bad impact on human life, such as destroying household relationships, increasing the spread of sexually transmitted diseases (STDs) and worse. is the decline in the morality of children and teenagers, especially when these children and teenagers take on the role of providing online prostitution services. The involvement of children and teenagers in the online prostitution industry is of course caused by various factors such as internal factors of children and teenagers and external factors of children and teenagers which position them as victims but without realizing it, they instill the value of fairness in children and teenagers in the implementation of the online prostitution industry, thereby encouraging them to have a role. active in the sustainability of the online prostitution industry. This thesis presents an answer to the role of child victims in the occurrence of online prostitution (MiChat) as viewed from the perspective of Victims Precipitation Theory. The existence of such problems aims to provide a position for this thesis as an academic support to provide a complete description regarding the role of child victims in the occurrence of online prostitution (MiChat) from the perspective of Victims Precipitation Theory. The method used in writing this thesis is a descriptive empirical legal research method. The results found were that child victims play an active role as providers of online prostitution services. This active role can be seen by the active actions of child victims promoting their services on the MiChat application by posting activities or photos of themselves that lead to things of a sexual nature so that when compared with the Victims Precipitation Theory, it can be said that the child victims are positioned as provocative victims.Keywords: Children; Online Prostitution; Victims Precipitation Theory  Abstrak  Kemajuan teknologi memberikan berbagai manfaat bagi kehidupan manusia. Salah satu manfaat yang di dapat melalui kemajuan dan perkembangan teknologi adalah keluasan akan akses informasi peristiwa, informasi pembelajaran hingga pada informasi perdagangan barang dan jasa hanya melalui satu atau beberapa aplikasi. Namun keluasan akan akses tersebut juga berdampak buruk pada kehidupan sosial di mana melalui keleluasaan tersebut memudahkan setiap orang untuk melakukan transaksi prostitusi secara online, hal ini berdampak buruk bagi kehidupan manusia seperti rusaknya hubungan rumah tangga, meningkatnya penyebaran Penyakit Menular Seksual (PMS) dan parahnya lagi adalah turunnya moralitas anak dan remaja terlebih ketika anak dan remaja tersebut mengambil peran sebagai penyedia jasa prostitusi online. Terlibatnya anak dan remaja dalam industri prostitusi online tentunya disebabkan berbagai faktor seperti faktor internal anak dan remaja dan faktor eksternal anak dan remaja yang memposisikan mereka sebagai korban namun tanpa disadari menanamkan nilai kewajaran kepada anak dan remaja dalam terlaksanakannya industri prostitusi online sehingga mendorong mereka agar memiliki peranan aktif dalam keberlanjutan industri prostitusi online. Skripsi ini hadir dengan menjawab bagaimana peran anak korban dalam terjadinya prostitusi online (MiChat) yang ditinjau dari sudut pandang Victims Precipitation Theory. Adanya permasalahan yang demikian bertujuan agar memberikan kedudukan bagi skripsi ini sebagai salah satu sandaran akademis untuk memberikan deskripsi secara utuh terkait dengan peran anak korban dalam terjadinya prostitusi online (MiChat) dalam perspektif Victims Precipitation Theory. Metode yang digunakan dalam penulisan skripsi ini adalah metode penelitian hukum empiris yang bersifat deskriptif. Hasil yang ditemukan adalah anak korban berperan aktif sebagai penyedia jasa prostitusi online, peranan aktif tersebut dapat dilihat dengan tindakan aktif anak korban mempromosikan jasanya di aplikasi MiChat dengan cara memposting kegiatan-kegiatan atau foto-foto dirinya yang mengarah kepada hal-hal yang bersifat seksualitas sehingga jika disandingkan dengan teori Victims Precipitation Theory maka dapat dikatakan bahwa anak korban tersebut berkedudukan sebagai provocative victims.Kata Kunci : Anak; Prostitusi Online; Victims Precipitation Theory